PELATIHAN PENULISAN AKSARA BALI PADA GURU SD GUGUS 7 KECAMATAN SUKASADA - I Gusti Agung Rai Jayawangsa; I Wayan Juliana; I Made Susila Putra; I Nengah Adi Widana; I Made Reland Udayana Tangkas; I Nyoman Suka Ardyasa (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
Importance of preserving Balinese Script (Aksara Bali) as a cultural heritage and identity of the Balinese community necessitates the implementation of local content curriculum at the Elementary School (SD) level. However, challenges arise due to the lack of teacher competence in mastering Balinese Script, particularly in the rules of pasang aksara(writing rules), stemming from insufficient material depth during their PGSD (Elementary School Teacher Education) college period. This impacts teaching methods, often making them rigid and focused on rote memorization rather than applicative skills. This research aims to improve the competence of Elementary School teachers in Cluster 7, Sukasada District in writing Balinese Script. The method used is quantitative with a One-Group Pretest-Posttest Design on a sample of 25 teachers. The three-day training included the delivery of aksara wreastra (basic script) and pasang aksara material, as well as practical manual exercises and the use of the interactive digital media Educaplay.com. The pretest results showed an initial average score of 72.5, with specific difficulty in pasang aksara (70). Following the training, the posttest results significantly increased to an average of 85 in both aspects (wangun and pasang aksara). The overall average increase of 17% is categorized as very good. In conclusion, this training program was successful in enhancing teachers' competence in Balinese Script writing. This improved competence is an essential asset for teachers to implement quality and sustainable Balinese Script learning in their respective schools, ensuring effective cultural preservation efforts